Efektivitas Hukum Terhadap Pemilihan Suara Ulang Dalam Pemilihan Umum di Kabupaten Wajo - Martono; Sulaeman; Baso Hamarullah; Riska Apriyani (YP-SDI Lamaddukelleng, 2025)
Revoting (PSU) is a procedure regulated in Law Number 7 of 2017 concerning General Elections, specifically in Article 372 paragraph (1), which states that a revote at a polling station (TPS) can be implemented if a natural disaster and/or riot occurs that causes the voting results to be unusable or the vote count to be unable to be carried out. This study aims to analyze the factors that influence the effectiveness of law enforcement by the General Elections Commission (KPU) in organizing a revote in Wajo Regency and to identify public perceptions of its implementation. With a comprehensive analysis, it is hoped that innovative solutions can be found to overcome various obstacles, so that future elections can run better, more transparently, and accountably.